SOCIAL MEDIA AS A STRATEGY FOR DISEASE PREVENTION IN STUDENT’S LIFE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Today university students have faced various health problems which can impact seriously on academic performance and well-being. These challenges are accordingly related to progressive behavior which students develop gradually in learning process. Taking mental disorder which is acquired because of the daily assessments, cultural diversity, academic environment, financial concern, social adjustment and many others. This paper reflects the health behavior of students and application of social media use as disease prevention. An evidence-based analysis of social media use among students can benefit university health policy.